Talking it through : responses to sorcery and witchcraft beliefs and practices in Melanesia - Forsyth, Miranda; Eves, Richard (ANU Press, 2015)
The book is structured into three parts. The chapters in Part 1 discuss the social, economic and cultural dimensions to the belief in witchcraft and sorcery. Part 2 contains a number of chapters that deal with the legal dimensions to the belief in witchcraft and sorcery. Finally, the chapters in Part 3 explore some positive ways forward in overcoming one of the most problematic aspects of sorcery and witchcraft beliefs and practices today, namely sorcery accusation-related violence.